Effect of pH and Monensin on Glucose Transport by Fibrobacter succinogenes, a Cellulolytic Ruminal Bacterium - Chow, Jo May (1992)
Fibrobacter succinogenes S85, a cellulolytic ruminal bacterium, required sodium for growth and glucose uptake. Cells which were deenergized with iodoacetate (500 μM) could not take up [(14)C]glucose. However, deenergized cells which were treated with valinomycin, loaded with potassium, and diluted into sodium or sodium plus potassium to create an artificial electrical gradient (ΔΨ) plus a chemical gradient of sodium (ΔpNa) or ΔpNa alone transported glucose at a rapid rate. Cells which were loaded with potassium plus sodium and diluted into sodium (ΔΨ with sodium, but no ΔpNa) also took up glucose at a rapid rate. Potassium-loaded cells that were diluted into buffers which did not contain sodium (ΔΨ without sodium) could not take up glucose. An artificial ZΔpH which was created by acetate diffusion could not drive glucose transport even if sodium was present. The maximum rate and affinity of glucose transport (pH 6.7) were 62.5 nmol/mg of protein per min and 0.51 mM, respectively. S85 was unable to grow at a pH of less than 5.5, and there was little glucose transport at this pH. When the extracellular pH was decreased, the glucose carrier was inhibited, intracellular pH declined, the cells were no longer able to metabolize glucose, and ΔΨ declined. Monensin (1 μM) or lasalocid (5 μM) decreased intracellular ATP and dissipated both the ΔΨ and ΔpNa. Since there was no driving force for transport, glucose transport was inhibited. These results indicated that F. succinogenes used a pH-sensitive sodium symport mechanism to take up glucose and that either a ΔΨ or a ΔpNa was required for glucose transport.